Policies on the admission of students with human immunodeficiency virus or hepatitis B virus infection in Philippine dental schools - Agbisit, Shari Lei D.; Co, Karina Isabel F.; Rosanes, Rose Anne Q. (Research Adviser).
This study aims to determine the policies on admission of students with HIV or HBV infection in Philippine dental school.
All 27 dental schools in the Philippines were chosen as the respondents of the study. A pilot test was done before data gathering. Informed consents were acquired prior to inclusion in the study and survey questionnaires were used to gather data.
Out of 27 dental schools, only 13 schools responded. Only three schools have a policy on admission of HBV-infected students and two schools have a policy on admission of HIV-infected students. Four schools (30.77%) do not allow admission of HBV-infected students and four (30.77%) do not allow HIV-infected students. Nine schools (69.23%) evaluate HBV-infection status but two out of nine (22.22%) do not evaluate routinely. Two schools (15.38%) evaluate HIV-infection status annually. HBV immunization is mandatory prior to admission in seven schools (53.85%) and prior to clinical practice in 10 schools (76.92%). Continuation of the course upon diagnosis of infection is allowed of HBV-infected students in seven schools (53.85%) and is allowed for HIV-infected students in two schools (15.38%). Seven schools (53.85%) offer assistance to transfer for HBV-infected students and five (38.46%) offer assistance to transfer HIV-infected students.
Only three out of 13 schools which responded have a policy on the admission of students with HBV and only two schools have the policy on admission of students with HBV and HIV. Their policies serve as the baseline data.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: HIV; Hepatitis B Virus; Human Immunodeficiency Virus; Admission in dental schools; Policies; Periodontal diseases